AB0243 Real world clinical trial comparing the patient reported outcomes measurement information system short forms and profiles to cdai disease classification in rheumatoid arthritis patients. (12th June 2018) - Curtis, J.; Schwartzman, S.; Kafka, S.; Parenti, D.; Black, S.; Xu, S.; Langholff, W.; Bingham, C.O.
Abstract : Background: Pt reported outcomes (PROs) play a role in disease evaluation, therapeutic assessment and care of RA pts. The Pt Reported Outcomes Measurement Information System (PROMIS [P]) questionnaires developed by NIH have been used in RA clinical practice and studies. Bartlett 2015 AWARE (Comparative and Pragmatic Study of Golimumab Intravenous [IV] Versus Infliximab in RA) is a noninterventional, multi-centre US-based, study of golimumab IV (GLM) vs. infliximab (IFX) in RA and will assess disease activity (DA) and use PROs. Objectives: 1. PRO assessments of Pt response to treatment using PROMIS-29 Profile v2.0 (P29v2), P Pain Interference Short Form-6b (PISF) and P Fatigue Short Form-7a (FSF), and Clinical DA Index (CDAI), and 2. assess relationship between PROMIS T-score and CDAI category. Methods: AWARE is a 1200 adult pt study enrolling pts on initiation of treatment w/GLM or IFX. We report an interim analysis (IA) of 747 pts' baseline PROMIS questionnaire and CDAI scores. PROMIS results are normalised to the US population, reported as a "T-score" (mean=50, SD=10) w/higher scores indicating more of the trait measured. PROMIS T–scores were compared between High DA (HDA) w/Moderate DA (MDA), low DA (LDA) and remission. Data shown are mean ±SD. Statistical testing compared T-scores across CDAI categories using ANOVA for these data (before drug admin). Data from GLM and IFX pts are combined. Results: Mean baseline CDAI score was 32.5±15.4, w/71.7% of pts in HDA, 22.5% in moderate MDA, 5.2% in LDA and 0.7% in remission. PROMIS T-scores were compared to 4 CDAI categories. HDA Pt T-scores were (*, p<0.05) different from those of MDA, LDA and Remission pts (except between HDA and remission for Anxiety, Depression and Sleep Disturbance domains). Conclusions: Our interim findings demonstrate the feasibility of using PROMIS short forms and profiles to evaluate RA Pts in clinical trials. These results confirm the domain validity of PROMIS measures according to CDAI DA category. PROMIS measures show the range of impact across multiple domains of physical, emotional, and social health experienced by RA Pts. Disclosure of Interest: J. Curtis Grant/research support from: Janssen Scientific Affairs, LLC, S. Schwartzman Grant/research support from: Janssen Scientific Affairs, LLC, S. Kafka Employee of: Janssen Scientific Affairs, LLC, D. Parenti Employee of: Janssen Scientific Affairs, LLC, S. Black Employee of: Janssen Scientific Affairs, LLC, S. Xu Employee of: Janssen Research and Development, LLC, W. Langholff Employee of: Janssen Research and Development, LLC, C. Bingham III Grant/research support from: Janssen Scientific Affairs, LLC